Pola Asuh Yang Tepat Di Masa Pandemi Covid 19 - Ampun Bantali (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
This journal will discuss fun parenting during a pandemic. This journal aims to describe how parenting patterns are used during the COVID-19 pandemic, so as to create healthy behavior in children, both physically and mentally, even during the Covid-19 disaster. The method used in writing this article is to use a literature review. The results of this article indicate that a fun parenting pattern during the Covid-19 pandemic must prioritize authoritative parenting. This is because during the Covid-19 pandemic, parents have an extra role to play in assisting children to learn online. In this case, of course, parents are required to have appropriate and pleasant parenting in accompanying children while at home. Good behavior emerges from good parenting, and vice versa.